2018
DOI: 10.1038/s41467-018-07549-4
|View full text |Cite
|
Sign up to set email alerts
|

Formation of electron radiation belts at Saturn by Z-mode wave acceleration

Abstract: At Saturn electrons are trapped in the planet’s magnetic field and accelerated to relativistic energies to form the radiation belts, but how this dramatic increase in electron energy occurs is still unknown. Until now the mechanism of radial diffusion has been assumed but we show here that in-situ acceleration through wave particle interactions, which initial studies dismissed as ineffectual at Saturn, is in fact a vital part of the energetic particle dynamics there. We present evidence from numerical simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 31 publications
2
57
0
Order By: Relevance
“…Roussos et al () demonstrated that transport time scales from the middle magnetosphere to Saturn's electron radiation belts due to time‐variable electric fields with a fixed local time pattern are on the order of 1–2 weeks. A competing process of wave‐driven acceleration requires time scales of ∼ 1 day (Woodfield Glauert et al, ) around L =5 to ∼100 days (Woodfield Horne et al, ) much further in. The convection and wave acceleration time scales are comparable at L >5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roussos et al () demonstrated that transport time scales from the middle magnetosphere to Saturn's electron radiation belts due to time‐variable electric fields with a fixed local time pattern are on the order of 1–2 weeks. A competing process of wave‐driven acceleration requires time scales of ∼ 1 day (Woodfield Glauert et al, ) around L =5 to ∼100 days (Woodfield Horne et al, ) much further in. The convection and wave acceleration time scales are comparable at L >5.…”
Section: Resultsmentioning
confidence: 99%
“…Adiabatic transport could be accomplished through stochastic magnetic field fluctuations (Roussos et al, ), centrifugal interchange instability injections (Azari et al, ; Paranicas et al, ; Rymer et al, ), or variable global scale convective flows (Roussos et al, ). Nonadiabatic mechanisms contributing to electron acceleration such as wave particle interactions (Horne et al, ) have been discussed by Woodfield Horne et al (, ) through numerical simulations and Cassini measurements. They presented that Z mode and chorus waves could accelerate electrons to megaelectron volt energies inside 7 R S through cyclotron resonant interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Losses could be due to collisions with the neutral torus and ring particles (which are slow, continuous losses; Woodfield et al, ; Lorenzato et al, ) or as yet unquantified wave‐particle interactions, particularly scattering due to whistler mode hiss (Menietti et al, ) and ion cyclotron waves (Leisner et al, ; Meeks et al, ). Recent results outside of 4 R S (Kollmann et al, ) show that electron energy spectra are time variable on top of a trend that follows the effect of radial diffusion; some of this variation may be due to chorus wave acceleration and subsequent losses.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The electron radiation belts at Saturn until recently were thought to be the result of the production of high‐energy electrons from Cosmic Ray Albedo Neutron Decay and radial diffusion of lower‐energy seed population electrons (Kollmann et al, ; Kollmann et al, ; Roussos et al, ). Recently, however, Woodfield et al () showed that wave‐particle interactions with Z‐mode waves have a very important role in accelerating electrons inside the orbit of Enceladus. Whistler mode chorus waves, which are a key source of electron acceleration at the Earth (Horne et al, ) and Jupiter (Horne et al, ; Woodfield et al, ), were dismissed as having negligible effect on the electrons at Saturn due to the combination of plasma and magnetic field conditions (Lorenzato et al, ; Shprits et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we adopt a dipole magnetic field to approximate the Saturn's background magnetic field (Gu et al, 2013;Woodfield et al, 2018).…”
Section: Plasma Density and Wave Modelsmentioning
confidence: 99%